The Analysis of Influence of Environmental Performance and Environmental Costs on Financial Performance with Corporate Social Responsibility as Intervening Variables: an Empirical Study on Mining Companies Listed on The Indonesia Stock Exchange - Rita JD Atarwaman (Jurnal Mantik, 2022)
This study aims to determine how much influence the environmental performance and environmental costs on financial performance with Corporate Social Responsibility as an intervening variable . The independent variables in this study are environmental performance and environmental costs. The dependent variable in this study is Financial Performance. The intervening variable in this research is Corporate Social Responsibility . The data in this study are secondary data obtained from the company's financial statements mining companies that follow PROPER and are listed on the IDX . The results showed that environmental performance had no effect on financial performance. Environmental costs have a significant positive effect on financial performance. Corporate social responsibility has a significant positive effect on financial performance. Environmental performance has a significant positive effect on Corporate Social Responsibility (CSR). Environmental costs have no effect on Corporate Social Responsibility (CSR). Corporate Social Responsibility (CSR) as an intervening variable is able to mediate the influence of environmental performance on financial performance . Corporate Social Responsibility (CSR) as an intervening variable is not able to mediate the effect of environmental costs on financial performance.